Using the otolith sulcus to aid in prey identification and improve estimates of prey size in diet studies of a piscivorous predator. Issue 8 (23rd March 2020) - Byrd, Barbie L.; Hohn, Aleta A.; Krause, Jacob R.
Abstract: Diet studies are fundamental for understanding trophic connections in marine ecosystems. In the southeastern US, the common bottlenose dolphin Tursiops truncatus is the predominant marine mammal in coastal waters, but its role as a top predator has received little attention. Diet studies of piscivorous predators, like bottlenose dolphins, start with assessing prey otoliths recovered from stomachs or feces, but digestive erosion hampers species identification and underestimates fish weight (FW). To compensate, FW is often estimated from the least affected otoliths and scaled to other otoliths, which also introduces bias. The sulcus, an otolith surface feature, has a species‐specific shape of its ostium and caudal extents, which is within the otolith edge for some species. We explored whether the sulcus could improve species identification and estimation of prey size using a case study of four sciaenid species targeted by fisheries and bottlenose dolphins in North Carolina. Methods were assessed first on otoliths from a reference collection ( n  = 421) and applied to prey otoliths ( n  = 5, 308) recovered from 120 stomachs of dead stranded dolphins. We demonstrated in reference‐collection otoliths that cauda to sulcus length (CL:SL) could discriminate between spotted seatrout ( Cynoscion nebulosus ) and weakfish ( Cynoscion regalis ) (classification accuracy = 0.98). This method confirmed for the first time predation of spotted seatrout by bottlenose dolphins in North Carolina. Using predictive models developed from reference‐collection otoliths, we provided evidence that digestion affects otolith length more than sulcus or cauda length, making the latter better predictors. Lastly, we explored scenarios of calculating total consumed biomass across degrees of digestion. A suggested approach was for the least digested otoliths to be scaled to other otoliths iteratively from within the same stomach, month, or season as samples allow. Using the otolith sulcus helped overcome challenges of species identification and fish size estimation, indicating their potential use in other diet studies. Abstract : We demonstrated that the otolith sulcus could improve prey identification and limit the bias of digestive erosion in diet studies where correction factors are not available using a case study of four fish species (Family Sciaenidae) targeted by fisheries and common bottlenose dolphins ( Tursiops truncatus ) along the US Atlantic coast.